Is There Room in the Inn?: Visiting Adoption in Herman Bavinck’s Ordo Salutis - Parker Gregory; Clausing Cameron (Perichoresis: The Theological Journal of Emanuel University, 2024)
In the theological retrieval of neo-Calvinism, Herman Bavinck (1854-1921) is the golden child, but does he ere? This article explores a misnomer in Bavinck’s theology, that of adoption within the ordo salutis (order of salvation). Bavinck’s doctrine of adoption seems to be misplaced because he writes of adoption as juridical (RD IV, 219, 226-227), a term that belongs properly to justification. Yet he draws upon adoption to illustrate sanctification. The two doctrines, justification and sanctification, are of course intimately linked in his system, but Bavinck either misdeploys or mis-categorizes adoption. In light of Bavinck, placing it in the juridical category, but drawing upon it to illustrate sanctification it remains unclear why it remains juridical. First, the article explores the main contours of Bavinck’s ordo salutis establishing the main categories and ordering, this will lay hold to the problematic placement of adoption. From there, a constructive alternative is set forth, that of the category of relational.